Дослідження моделей і методів автоматизації планування роботи команди виконавців ІТ-проєкту - Дудка, М. В. (ХНУРЕ, 2023)
This work presents an analysis of the existing problem of resource planning between projects and the selection of resources in a company and team. An analysis of existing systems is given and potential options are indicated with a description of their shortcomings. The argument in favor of using a mathematical model for such a system is also given